Pooled Nucleic Acid Testing to Detect Antiretroviral Treatment Failure in HIV-Infected Patients in Mozambique. (1st November 2015) - Tilghman, Myres; Tsai, Daniel; Buene, Titos P.; Tomas, Manuel; Amade, Salma; Gehlbach, Daniel; Chang, Stephanie; Ignacio, Caroline; Caballero, Gemma; Espitia, Stephen; May, Susanne; Noormahomed, Emilia V.; et al.
Abstract : Background: In resource-limited settings, viral load monitoring of HIV-infected patients receiving antiretroviral therapy (ART) is not readily available because of high costs. Here, we compared the accuracy and costs of quantitative and qualitative pooled methods with standard viral load testing. Methods: Blood was collected prospectively from 461 patients receiving first-line ART in Mozambique who had not been evaluated previously with viral load testing. Screening for virologic failure of ART was performed quantitatively (ie, standard viral loads) and qualitatively [one and 2 rounds of polymerase chain reaction (PCR)]. Individual samples and minipools of 5 samples were then analyzed using both methods. The relative efficiency, accuracy, and costs of each method were calculated based on viral load thresholds for ART failure. Results: Standard viral load testing of individual samples revealed a high rate of ART failure (19%–23%) across all virologic failure thresholds, and the majority of the patients (93%) with viral loads >1500 copies per milliliter had genotypic resistance to drugs in their ART regimen. Pooled quantitative screening and deconvolution testing had positive and negative predictive values exceeding 95% with cost savings of 11, 250 compared with quantitative testing of each sample individually. Pooled qualitative screening and deconvolution testing had a higher cost savings of 30, 147 for 1 PCR round and 25, 535 for 2 PCR rounds compared with quantitative testing each sample individually. Both pooled qualitative PCR methods had positive and negative predictive values ≥90%, but the pooled 1-round PCR method had a sensitivity of 64%. Conclusions: Given the high rate of undiagnosed ART failure and drug resistance in this cohort, it is clear that virologic monitoring is urgently needed in this population. Here, we compared alternative methods of virologic monitoring with standard viral load testing of individual samples and found these methods to be cost saving and accurate. The test characteristics of each method will likely need to be considered for each local population before it is adopted.